Deciphering the worlds of Hebrews collected essays - Gelardini, Gabriella 1964- (Leiden Boston Brill, 2021)
Introduction: Hebrews Scholarship in the 19th and 20th Century -- 1 Hebrews Scholarship in the 21st Century -- 2 Arrangement and Content of This Collection -- part 1: The World of Hebrews's Text -- 1 "As if by Paul?" Some Remarks on the Textual Strategy of Anonymity in Hebrews -- 1 Introduction-Hebrews: Pauline or not Pauline, or "Somehow" Connected to a Pauline Environment -- 2 Anonymity as a Literary Strategy -- 3 Habakkuk 2:4 in Hebrews and Paul -- 4 Jesus as Mercy Seat (ἱλαστήριον) in Heb 9:5 and in Rom 3:25? -- 5 Once for All (ἐφάπαξ) in Hebrews and Paul -- 6 Brief Conclusion -- 2 From "Linguistic Turn" and Hebrews Scholarship to Anadiplosis Iterata : The Enigma of a Structure -- 1 History of Ideas -- 2 Hebrews Scholarship in the Twentieth and Twenty-First Centuries -- 3 Structural Analysis: A New Proposal -- 3 Hebrews, Homiletics, and Liturgical Scripture Interpretation -- 1 The Ancient Synagogue and its Liturgy -- 2 The Ancient Synagogue Homily -- 3 The Two Readings Underlying Hebrews, or its Two Central Scriptural Quotations -- 4 Hebrews, an Ancient Synagogue Homily and its Remaining Scriptural Quotations -- 5 Hebrews in the Context of Ancient Synagogue Liturgy -- 4 Hebrews, an Ancient Synagogue Homily for Tisha Be-Av: Its Function, Its Basis, Its Theological Interpretation -- 1 Introduction -- 2 The Ancient Synagogue Homily in Its Liturgical Context -- 3 Hebrews, an Ancient Synagogue Homily for Tisha be-Av -- 4 Conclusion -- 5 Rhetorical Criticism in Hebrews Scholarship: Avenues and Aporias -- 1 A Brief History -- 2 Exemplary and Theoretical Analysis -- 3 Summary and Prospects -- part 2: The World behind Hebrews's Text -- 6 Frei von Blut und Fleisch, Sündenbewusstsein und Todesfurcht: Die Hoffnung auf einen vollkommenen Menschen im Hebräer -- 1 Einleitung -- 2 Der kosmische Horizont des Menschenbilds im Hebräer -- 3 Jesus Christus ist der Mensch-die "christologische" Anthropologie -- 4 Blut und Fleisch, Seele und Geist, Tod und Leben.
5 Geheiligtes Menschsein muss noch im Glauben der Erprobung im Leiden standhalten -- 6 Versuch einer historischen Kontextualisierung -- 7 Schluss -- 7 Charting "Outside the Camp" with Edward W. Soja: Critical Spatiality and Hebrews 13 -- 1 Introduction -- 2 Hebrews 13 in Scholarship: Riddles about a Key Space -- 3 Critical Spatiality: An Apt Methodology -- 4 The Text of Hebrews 13: Overlapping Maps -- 5 The Primary Intertext of Hebrews 13: Exodus 32-33 -- 6 How the Primary Intertext, Exodus 32-33, Reinterprets Hebrews 13 Spatially -- 7 Conclusion and Outlook -- 8 Useless Foods: Communal Meals in Hebrews -- 1 Introduction -- 2 The Epistle to the Hebrews and Communal Meals -- 3 Context, Structure and Content -- 4 Research History and Central Intertext -- 5 How the Intertext Exod 32-34 Interprets Heb 13 -- 6 Conclusion -- 9 Von Bundesbruch zu Bundeserneuerung: Das sühnende Opfer im Hebräer -- 1 Das Opfer im Neuen Testament und im Hebräer -- 2 Der kultisch-liturgische Kontext des Hebräers -- 3 Der theologische Kontext des Hebräers -- 4 Die kultischen Inhalte des Hebräers -- 5 Der sühnende Opferkult des Jom Kippur -- 6 Der sühnende Opferkult im Hebräer -- 7 Der historische Kontext des Hebräers -- 10 The Inauguration of Yom Kippur according to the LXX and Its Cessation or Perpetuation according to Hebrews: A Systematic Comparison -- 1 Introduction -- 2 Hebrews Scholarship -- 3 Systematic Comparison of Cultic Elements -- 4 Conclusion -- part 3: The World in Front of Hebrews's Text -- 11 Faith in Hebrews and Its Relationship to Soteriology: An Interpretation in the Context of the Concept of Fides in Roman Culture -- 1 Fides quaerens intellectum? -- 2 Bicultural Interaction, Not Syncretism -- 3 Fides and πίστις -- 4 The Cloud of Witnesses -- 12 Existence beyond Borders: Hebrews and Critical Spatiality -- 1 The Turn to Critical Spatiality -- 2 Mapping the Ancient World with Hebrews.
3 "Outside the Camp": A "Counter Space" in Heb 13 -- 13 "Wir haben hier keine bleibende Stadt" (Hebr 13,14): Kritische Raum- und Machtdiskurse im Hebräer -- 1 Die Wende zur Raumsoziologie ("Critical Spatiality") -- 2 Eine Landkarte der Alten Welt: Nach dem Neuen Testament und dem Hebräerbrief -- 3 "Ausserhalb des Lagers"-Ein "Gegenort" in Hebr 13 -- 14 The Unshakeable Kingdom in Heaven: Notes on Eschatology in Hebrews -- 1 Introduction-Eschatology and Apocalypticism -- 2 Hellenistic and Apocalyptic Eschatology in the Epistle to the Hebrews -- 3 The Unshakeable Kingdom of Heaven -- 15 Ethics in Hebrews -- 1 Introduction -- 2 Descriptions of Hebrews's Ethics -- 3 Ethical-Hermeneutical Evaluations of Hebrews -- 4 Conclusion -- Index of Ancient Sources -- Index of Modern Authors.
In the collection entitled Deciphering the Worlds of Hebrews Gabriella Gelardini gathers fifteen essays written in the last fifteen years, twelve of which are in English and three in German. Arranged in three parts (the world of , behind , and in front of Hebrews's text), her articles deal with such topics as structure and intertext, sin and faith, atonement and cult, as well as space and resistance. She reads Hebrews no longer as the enigmatic and homeless outsider within the New Testament corpus, as the "Melchizedekian being without genealogy"; rather, she reads Hebrews as one whose origin has finally been rediscovered, namely in Second Temple Judaism
Includes bibliographical references and index
Twelve essays in English, and three in German
Keywords: Bible -- New Testament